The The Correlation Between Students’ Personalities (Extrovert and Introvert) and Their Speaking Skills at Eleventh Grade of MAN 1 Mamuju - Fatmawati Fatmawati; Adzima Nurul Fatimah (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
The objective of the research was to find out the correlation between students’ introvert personality and their speaking skills at MAN 1 Mamuju. In conducting this research, the researcher has collected the data using correlational research. The data was collected through questionnaire, interview and speaking test. The researcher used purposive sampling in determining the research sample. There were 40 students consisted of 20 extrovert and 20 introvert students that had been divided by using the MBTI Personality Questionnaire by Dartmouth Hitchcock Medical Center to acquire the data needed. The data were analyzed by using SPSS 22.0 that consist of Normality Test, Pearson Product Moment. the result of this research showed that there was no correlation between students' personalities (extrovert and introvert) and their speaking skills. According to the result of statistical calculation, it could be seen that the correlation score was -0.082 smaller compared to r-table at the significant degree 5% (0.312). Thus, the alternative hypothesis (Ha) was rejected and null hypothesis (H0) was accepted. In conclusion there is no correlation between students' personalities (extrovert and introvert) and their speaking skills.